Origins of native vascular plants of Antarctica: comments from a historical phytogeography viewpoint - Mosyakin, S.L.; Bezusko, L.G.; Mosyakin, A.S. (Цитология и генетика, 2007)
The article provides an overview of the problem of origin of the only native vascular plants of Antarctica, Deschampsia antartica (Poaceae) and Colobanthus quitensis (Caryophyllaceae), from the viewpoint of modern historical phytogeography and related fields of science. Дан обзор проблемы происхождения аборигенных сосудистых растений Антарктики Deschampsia antartica (Poaceae) и Colobanthus quitensis (Caryophyllaceae) с точки зрения исторической фитогеографии и родственных направлений науки. Подається огляд проблеми походження єдиних аборигенних судинних рослин Антарктики Deschampsia antarctica (Poaceae) та Colobanthus quitensis (Caryophyllaceae) з точки зору історичної фітогеографії та споріднених напрямків науки.